Geometric issues and ultimate load capacity of masonry arch bridges from the Northwest Iberian Peninsula - Oliveira, Daniel V. (2010)
This paper reports the results from a geometrical survey carried out on 59 segmental masonry arch bridges from Portugal and Spain, with a focus on the adjacent geographical areas of northern Portugal and north-western Spain. Historical empirical rules are briefly presented and further compared against the bridges’ geometrical data. Departing from a detailed discussion of the geometrical results, eight reference bridges were defined as representative of the sample. Subsequently, the paper deals with a parametric assessment of the load-carrying capacity of the reference bridges and a discussion of results. It was found that arch thickness and physical properties of the fill are of paramount importance in terms of ultimate load-carrying capacity. Furthermore, the results indicate that the bridges from the sample are structurally safe with respect to applicable legislation.